The new home : a handbook for tenants (London : The Health and Cleanliness Council, 1937)
1937 1937 1930s 24 pages : illustrations mattress, blankets, pillows and eiderdowns. Useful hints on washing bed linen will be found on page 19, "Hints for the Busy Housewife," copies of which may be obtained from the Health and Cleanliness Council, Tavistock Square, London, W.C.1. GOOD LIGHTS FOR READING IN BED If you like reading in bed, arrange an electric light over the bed head, preferably a modern one which is actually attached to the bed. The light should be shaded, so that the rays all fall downwards. [illustration] The comfort of electric bed lights. POLISHED FLOORS ARE BEST Rugs at the bedside and in front of the dressing table or chest of drawers are sufficient covering for the bedroom floor; but if you have a carpet see that it is vacuumed frequently. Stains can be removed by washing with carpet soap and water (see "Hints for the Busy Housewife," page 8). AS LITTLE FURNITURE AS POSSIBLE It is not necessary to have much furniture in the bedrooms, and it is suggested that the bed, dressing table, wardrobe, chest of drawers, and a small chair are sufficient. Don't put mats on the dressing table and chest of drawers; these look much nicer bare if they are kept well polished. Under-furnishing is no crime. Over-furnishing means overwork. THE USE OF CHAMBERS If chambers are used in the bedroom, great care should be taken to see that they are emptied and washed thoroughly clean with hot water and a good soap-powder, then rinsed out with cold water every day. Many people nowadays rely entirely upon the lavatory and mothers train their young children to use this. 12 177/5/8/2